Ducaches in the ukrainian culture area - VOLIK, KATYA (Journal of Education Culture and Society, 2020)
The report describes the emergence (origin) and distribution of dukachey in the Ukraine, their popularity and distribution, and why they have been largely forgotten.The report examines dukach - traditional ukrainian folk decoration. It is considered one of the branches of folk art - namely, the tradition of folk ornaments in the example of ducats.It examines the role of dukachey in the material and spiritual life of the Ukrainians. Appeal to the national art and national traditions is a means of creating a cultural identity and national consciousness.The in uence of cultural traditions dukacha Ukrainians. The diversity of national cul-tures enriches the culture of the world, and shows the universal and the particular, inherent in a particular culture.The report investigates the artistic means of the expression of dukachey based on tech-nical and technological characteristics of the production of coin-dukachey.